Epidemiological insights into hospital admissions for migraines and other headache disorders in a Central-West City of Paraná - Miranda, Livia Hoyer Garcia; Valério, Catharina Delazari; Tomasi, Gustavo Henrique (Headache Medicine, 2024)
Introduction: According to the WHO, half of the world's population experiences headaches at some point. Understanding the epidemiology of such a prevalent and debilitating disease is essential for developing policies, organizing healthcare services, identifying associated factors, and assessing public health impacts. Therefore, knowing the epidemiology of headaches in Guarapuava, Paraná is crucial for devising effective clinical management and prevention strategies. Objectives: Analyze the epidemiological profile of migraines and headaches in Guarapuava, Paraná, from 2009 to 2023. Methodology: Analytical and retrospective study using data from the SUS Hospital Information System on hospitalizations for migraines and other headaches, without specifying differential diagnoses among pain syndromes, in Guarapuava, Paraná (2009-2023). The study included male and female individuals aged 5 to 80 years or older. Results: During the period assessed, 178 hospitalizations were reported, with 6 (3.37%) elective and 172 (96.62%) emergency cases. Average stay was 3.2 days, with a total cost of R$ 40,608.63. Of the patients, 52 (29.2%) were male and 126 (70.8%) female, including 2 (1.12%) aged 5-9 years, 16 (8.98%) aged 10-14 years, 15 (8.42%) aged 15-19 years, 28 (15.73%) aged 20-29 years, 35 (19.66%) aged 30-39 years, 31 (17.41%) aged 40-49 years, 24 (13.48%) aged 50-59 years, 15 (8.42%) aged 60-69 years, 9 (5.05%) aged 70-79 years, and 3 (1.68%) aged 80 years or older. Conclusion: Analysis of data on hospitalizations for headaches in Guarapuava provides insights into epidemiology, economic impact, and demographic characteristics. Most hospitalizations were among females, possibly due to hormonal, genetic, and social factors. The age distribution shows a peak between ages 30 to 49, comprising 37% of cases. A notable number of hospitalizations were also seen among adolescents (17.4%), underscoring headaches as a public health concern across age groups. The high percentage of emergency admissions (96.62%) suggests urgent hospital care needs, reflecting symptom severity or inadequate outpatient management. Understanding specific diagnoses within painful syndromes is crucial. Strategies to improve clinical management and reduce hospitalization costs are necessary for effective health policies addressing prevention and treatment of headaches.